The incidence of nominal and real wage rigidity: an individual-based sectoral approach - Julián Messina; Philip Du Caju; Mario Izquierdo; Cláudia Filipa Duarte; Niels Lynggård Hansen (European Central Bank (ECB), 2010)
This paper presents estimates based on individual data of downward nominal and real wage rigidities for thirteen sectors in Belgium, Denmark, Spain and Portugal. Our methodology follows the approach recently developed for the International Wage Flexibility Project, whereby resistance to nominal and real wage cuts is measured through departures of observed individual wage change histograms from an estimated counterfactual wage change distribution that would have prevailed in the absence of rigidity. We evaluate the role of worker and firm characteristics in shaping wage rigidities. We also confront our estimates of wage rigidities to structural features of the labour markets studied, such as the wage bargaining level, variable pay policy and the degree of product market competition. We find that the use of firm-level collective agreements in countries with rather centralized wage formation reduces the degree of real wage rigidity. This finding suggests that some degree of decentralization within highly centralized countries allows firms to adjust wages downwards, when business conditions turn bad.
Keywords: J31; 330; wage rigidity; wage-bargaining institutions; Lohnrigidität; Lohnstruktur; Lohnbildung; Tarifverhandlungen; Belgien; Dänemark; Portugal; Spanien